Thermal performance modeling of unglazed transpired solar collectors - Sadegh Motahar (مجله مدل سازی در مهندسی, 2018)
Unglazed transpired solar collectors (UTCs) are solar air heating collectors that used for preheating air in ventilation systems or producing hot air for drying systems. Thermal performance of UTCs is a function of various parameters including incident solar radiation, air approach velocity, diameter and pitch of perforations. Modeling predicts the thermal performance of UTCs over a wide range of design and operating conditions. This paper presents the details of modeling for UTC using heat transfer expressions for the collector components and energy balances. The effects of key parameters on the performance of a UTC were studied by varying the approach velocity, solar radiation, diameter and pitch of perforations and finding their influence on collector thermal efficiency, heat exchange effectiveness and outlet air temperature. Results showed that the UTC thermal efficiency increases by increase in solar radiation and approach velocity, but the efficiency decreases by increasing plate hole diameters and pitch.